1992
DOI: 10.7326/0003-4819-117-6-461
|View full text |Cite
|
Sign up to set email alerts
|

Patent Foramen Ovale as a Risk Factor for Cryptogenic Stroke

Abstract: Patients with cryptogenic stroke have a higher prevalence of patent foramen ovale than patients with stroke of determined cause in all age groups, even after correcting for the presence of recognized stroke risk factors. This identifies patent foramen ovale as a risk factor for cryptogenic stroke. Regardless of patient age, contrast echocardiography should be considered when the cause of stroke is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
275
2
11

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 553 publications
(298 citation statements)
references
References 23 publications
10
275
2
11
Order By: Relevance
“…[1][2][3][4] The number of patients in each report, however, was small. In this study, with a significantly larger number of patients, we confirm that PFO is associated with cryptogenic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The number of patients in each report, however, was small. In this study, with a significantly larger number of patients, we confirm that PFO is associated with cryptogenic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The association between PFO and cryptogenic stroke has been described from observational clinical trials. 16,17 However, appropriate therapy for these patients is still undetermined. The rate of recurrent TIA and stroke in patients with cryptogenic stroke is estimated at 3.8% to 5.5% per year despite adequate anticoagulation or antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Microspheres were detected in the epicardium of the left ventricle in two of our exercising dogs, suggesting that recruitment of I-P shunts could play a role in embolic heart disease. In addition, previous work has shown that stroke patients have a higher prevalence of patent foramen ovale (38)(39)(40), and hereditary hemorrhagic telangiectasia patients are more susceptible to embolic stroke and neurologic symptoms (41), indicating that blood flow bypassing the pulmonary microcirculation may have important physiological relevance. Isolated lung work has shown that I-P arteriovenous shunts are up to 420 m in diameter in the dog (11), 390 m in the cat (9), and 200 m in the adult human (13).…”
Section: Shunt Consequencementioning
confidence: 99%